2000
DOI: 10.1083/jcb.151.7.1353
|View full text |Cite
|
Sign up to set email alerts
|

Localized Biphasic Changes in Phosphatidylinositol-4,5-Bisphosphate at Sites of Phagocytosis

Abstract: Phagocytosis requires localized and transient remodeling of actin filaments. Phosphoinositide signaling is believed to play an important role in cytoskeletal organization, but it is unclear whether lipids, which can diffuse along the membrane, can mediate the focal actin assembly required for phagocytosis. We used imaging of fluorescent chimeras of pleckstrin homology and C1 domains in live macrophages to monitor the distribution of phosphatidylinositol-4,5-bisphosphate (4,5-PIP2) and diacylglycerol, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
530
0
9

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 489 publications
(568 citation statements)
references
References 59 publications
29
530
0
9
Order By: Relevance
“…In fact, such demarcations (i.e. steep gradients) for polyphosphoinositides are indeed observed at the borders of membrane ruffles 3 and nascent phagosomes (109,110). The interpretation of these experiments, however, is not straightforward because the probe used to detect the lateral organization of PIP 2 in the plasma membrane, the PH domain of PLC-␦ 1 , is itself negatively charged when bound to PIP 2 , and a green fluorescent protein construct of this PH domain, like PIP 2 , is also electrostatically sequestered by the basic residues in the effector domain of MARCKS.…”
Section: Electrostatic Equipotential Profiles Of Membranes With or Wimentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, such demarcations (i.e. steep gradients) for polyphosphoinositides are indeed observed at the borders of membrane ruffles 3 and nascent phagosomes (109,110). The interpretation of these experiments, however, is not straightforward because the probe used to detect the lateral organization of PIP 2 in the plasma membrane, the PH domain of PLC-␦ 1 , is itself negatively charged when bound to PIP 2 , and a green fluorescent protein construct of this PH domain, like PIP 2 , is also electrostatically sequestered by the basic residues in the effector domain of MARCKS.…”
Section: Electrostatic Equipotential Profiles Of Membranes With or Wimentioning
confidence: 96%
“…Furthermore, MARCKS is not uniformly distributed in the plasma membrane of some cell types (103); it is concentrated in the membrane ruffles of fibroblasts (104) and, along with MacMARCKS, in the nascent phagosomes of macrophages (105,106). If MARCKS sequesters PIP 2 , this lipid should colocalize with MARCKS in these regions, and it does (107)(108)(109). However, elucidating the mechanism of colocalization is complicated by the fact that PIP 2 -producing kinases are also concentrated in ruffles and nascent phagosomes.…”
Section: Electrostatic Equipotential Profiles Of Membranes With or Wimentioning
confidence: 99%
“…Actin polymerization drives phagosome formation, and in other phagocytic cell types it has been reported that F-actin begins to depolymerize at or before the point at which phagosome closure is complete (May and Machesky, 2001). It has been proposed that phosphatidylinositol 4,5-bisphosphate (PtdIns4,5P 2 ) at the site of formation of the phagocytic cup and its subsequent hydrolysis as the cup closes are the key signaling events regulating the cycle of actin polymerization and depolymerization (Botelho et al, 2000;Scott et al, 2005). Because anx A2 is a potent regulator of actin dynamics (Merrifield et al, 2001;Hayes et al, 2006) and binds both cholesterol-rich membranes, Ca 2ϩ , and PtdIns4,5P 2 Rescher et al, 2004;Gerke et al, 2005), it is well placed to function as a sensor of these second messengers and signaling intermediates, linking .…”
Section: Discussionmentioning
confidence: 99%
“…on April 7, 2019. by guest www.bloodjournal.org From Interestingly, the reduction of PIP2 levels in the synapse area is reminiscent of PIP2 disappearance observed in forming phagosomes. 23,30 The contribution of individual metabolic pathways to PIP2 use is likely attributable to its enzymatic conversion into critical signaling intermediates, such as IP3 and diacylglycerol or PIP3, by PLC␥, and PI3K, respectively. However, PIP2 interaction with ligands with higher affinity may also contribute to the displacement of the probe during the cytolytic event.…”
Section: Pi5ki-dependent Signals 4169mentioning
confidence: 99%
“…29,30 Primary cultured NK cells were sorted by FACS to isolate cells expressing GFP-PH at high levels. Cell viability was not affected by PIP2 masking (F.M., unpublished data, January 15, 2006).…”
Section: The Reduced Availability Of Pip2 Is Associated With Impairmementioning
confidence: 99%